The impact of community-based learning programs on developing concepts of civic responsibility and intercultural sensitivity in female university students in Sudan - Osman, Azza Abdelmoneim (AUC Knowledge Fountain, 2020)
Community based learning (CBL) could be defined as a transformational learning approach that promotes students' civic participation and community engagement (Davidson, 2002). CBL’s main objectives are academic, professional, personal and social growth. Additional objectives include awareness of different social challenges impacting the community, and being socially responsible and active (Celio, Durlak, & Dymnicki, 2011). Given the rapid social, political and cultural change happening in recent years in Sudan, and that women in particular, have been given a reduced role in public life and leadership. An in-depth assessment of service learning and its role in developing positive personal, professional and civic engagement outcomes for female students is needed. This research explored how an intensive university CBL program influenced female university students' civic attitudes, personal and professional growth, and intercultural sensitivities. It further explored whether school discipline had an impact on the learning outcomes of CBL on students. Results showed that overall the learning outcomes for students were equally contributed between CBL and classroom knowledge. CBL positively influenced students’ civic engagement, personal growth and helped develop their professional skills. Meanwhile, students attributed development in their educational and academic skills more to their classroom knowledge. Both first year and fourth year students had high levels of intercultural sensitivity, yet there were no differences between students who experienced CBL and students who did not, on the Intercultural Sensitivity Scale (ISS) scale. Meanwhile, through the interviews students expressed high levels of intercultural sensitivity due to their CBL experiences. In terms of the learning outcomes of CBL, schools of Medicine, Pharmacy, and Management had better outcomes than school of Rural Extension Education and development (REED), Psychology and Health Sciences.